A chemometric approach for the segregation of bark biomass based on tree height and geographic location. (1st October 2020) - Raymond, Laura G.; Hill, Stefan J.; Grigsby, Warren J.; Bogun, Ben R.
Abstract: A chemometric approach is presented to differentiate and segregate bark biomass variability by proportionating the chemical functionality of components based on solid state NMR. Bark can vary from the tree base to the canopy, and as a biomass source, it would be desirable to assess and predict bark compositional variations to optimize biomass use. In this study, principal component analysis (PCA) was used to relate chemical compositions of various Pinus radiata pine barks with respect to tree height and geographic location, and after removal of water-soluble compounds. NMR spectra were bucketed to encompass major chemical functional groups and then PCA was applied. The analysis revealed sample clustering by tree height as was evident from the loadings plots and were attributed to phenolic, di- O -alkyl/aromatic, and O -alkyl regions. Bark samples were found to have distinct differences by tree height. These were dominated by chemical functional groups consistent with condensed tannins (polyphenols) and carbohydrate components, respectively. The analysis revealed no significant differences by geographic location. Similarly, hot water extracts and the extracted bark were distinguished by tree height based on their polyphenol and carbohydrate components.